Clinical and Epidemiological Characteristics of Japanese Spotted Fever and Scrub Typhus in Central Japan, 2004–2015. (4th October 2017) - Sando, Eiichiro; Suzuki, Motoi; Yaegashi, Makito; Taira, Masakatsu; Ogawa, Tomoko; Ariyoshi, Koya
Abstract: Background: Japanese spotted fever (JSF) and scrub typhus (ST) are endemic rickettsial diseases in Japan. Both diseases potentially have a fatal outcome. Since no studies have specifically compared JSF with ST, we investigated the clinical and epidemiological characteristics of JSF and ST in the area where both are endemic. Methods: We systematically collected clinical and epidemiological data from all patients clinically suspected with rickettsial diseases at three medical facilities in Boso Peninsula of Japan between 2004 and 2015. Indirect immunofluorescence assays were used, and eschar PCR/immunoperoxidase assays were also used for identifying the strain. SatScan™ was used for spatial cluster analysis. Results: In total, 661 patients were enrolled, 44% were female, and the mean age was 64 years. Thirty-two patients were diagnosed as JSF, 204 were ST, and 97 were non-rickettsial diseases. Only one patient died of ST. Comparing to non-rickettsial diseases, patients with JSF and ST were significantly older, and more of them resided wooded area ( P < 0.001). Spatial clusters were identified for both JSF ( P < 0.001) and ST ( P < 0.05). JSF occurred from April to October with a small peak in July, while 90.2% of ST was diagnosed in November and December. Both rash and eschar were detected in the majority of JSF (97%, 86%) and ST (96%, 87%). When compared with ST, purpura, and the rash on palms/soles were strongly associated with JSF (OR, 29.0, 61.1, respectively). However, patients were much less likely to complain their rash (27% JSF, 44% ST) and eschar (0% JSF, 2.5% ST). Moreover, 26% of JSF and 28% of ST cases did not present with apparent fever (≥37.5°C). All identified ST strains were Irie/Kawasaki (16/22, 73%) or Hirano/Kuroki (6/22, 27%). Conclusion: Although clinical picture of JSF and ST are similar, there are some clues to distinguish JSF from ST such as seasonality, geographical region, rash distribution on palms/soles, and the hemorrhagic nature of rash. Rickettsial cases may be underdiagnosed if clinical diagnosis relies on fever, rash, and eschar. Disclosures: All authors: No reported disclosures.